The Non-Hierarchical Way from Yijing to Jeongyeok: A New Paradigm for East Meeting West - Ko, Young Woon (Lexington Books, 2023)
The Non-Hierarchical Way from Yijing to Jeongyeok: A New Paradigm for East Meeting West examines the paradoxical structure of Yijing known as the Book of Changes—a structure that promotes in a non-hierarchical way the harmony and transformation of opposites. Because the non-hierarchical model is not limited to the East Asian tradition, it is considered in relation to ideas developed in the West, including Carl Jung’s archetypal psychology, Georg Cantor’s Diagonal Theorem, Rene Girard’s mimetic desire, and Alfred North Whitehead’s process thought. By critically reviewing the numerical and symbolic structures of Yijing, Young Woon Ko introduces Kim Ilbu’s Jeongyeok (the Book of Right Changes) and demonstrates that it intensifies the correlation between opposites to overcome any hierarchical system implied by the Yijing. Both the Yijing and the Jeongyeok are useful textual sources for kindling a discussion about the Divine, which is conceived in Eastern and Western philosophical theological traditions quite differently. While the nontheistic aspects of the Ultimate feature prominently in Yijing, Jeongyeok extends them to a theistic issue by introducing the notion of Sangjae, the Supreme Lord, which can lead to a fruitful dialogue for understanding the dipolar characteristics of the divine reality—personal and impersonal. Ko considers their contrast, which has divided Eastern and Western religious belief systems, to be transformational and open to a wider perspective of the divine conception in the process of change.